Voltage Imaging of Cardiac Cells and Tissue Using the Genetically Encoded Voltage Sensor Archon1 - Sanaya N. Shroff; Shoshana L. Das; Hua-an Tseng; Jad Noueihed; Fernando Fernandez; John A. White; Christopher S. Chen; Xue Han (iScience, 2020)
Summary: Precise measurement of action potentials (APs) is needed to observe electrical activity and cellular communication within cardiac tissue. Voltage-sensitive dyes (VSDs) are traditionally used to measure cardiac APs; however, they require acute chemical addition that prevents chronic imaging. Genetically encoded voltage indicators (GEVIs) enable long-term studies of APs without the need of chemical additions, but current GEVIs used in cardiac tissue exhibit poor kinetics and/or low signal to noise (SNR). Here, we demonstrate the use of Archon1, a recently developed GEVI, in hiPSC-derived cardiomyocytes (CMs). When expressed in CMs, Archon1 demonstrated fast kinetics comparable with patch-clamp electrophysiology and high SNR significantly greater than the VSD Di-8-ANEPPS. Additionally, Archon1 enabled monitoring of APs across multiple cells simultaneously in 3D cardiac tissues. These results highlight Archon1's capability to investigate the electrical activity of CMs in a variety of applications and its potential to probe functionally complex in vitro models, as well as in vivo systems. : Biotechnology; Bioelectronics; Technical Aspects of Cell Biology; Electronic Materials Subject Areas: Biotechnology, Bioelectronics, Technical Aspects of Cell Biology, Electronic Materials